The Relationship between Risk Propensity, Risk Perception and Risk-Taking Behaviour in an Emerging Market - Hamid, Fazelina Sahul; Rangel, Gary John; M. Taib, Fauziah; Thurasamy, Ramayah (Universiti Utara Malaysia, 2013)
This paper reports evidence to support a relationship between risk propensity, risk perception, and risk-taking behaviour of investors in an emerging market. Primary data were gathered using a validated structured questionnaire, which was self-administered by respondents: there were 162 investors from 8 stockbroking companies. A multiple regression was used to test the direct and indirect effects of the identified behavioural characteristics on investment decision. Risk propensity was found to be positively related to risk-taking behaviour whereas risk perception was negatively related to risk-taking behaviour.It was further found that risk perception partially mediates the effect of propensity to take risk. This suggests that the perceptual framing of a situational context in the investors’ thought processes reduces but it does not totally overwhelm the innate personality traits with respect to either the investor’s risk-seeking or risk-averseness. The tendency to engage in risky behaviour is more psychological in nature. The implications of the research are further explored.